The Immediate Effect of Parachute-Resisted Gallop on Heart Rate, Running Speed and Stride Frequency in Dogs - Hederstedt, Sandra (Animals (Basel), 2021)
SIMPLE SUMMARY: Physical fitness is needed for canine athletes and working dogs to optimize their performance in various disciplines. Application of resistance on movements causes biomechanical and cardiorespiratory responses to physical exercise. However, there is still a lack of research on the effects of high-intensity resistance exercise on cardiorespiratory fitness components such as heart rate in canine athletes. In this article, we investigate the short-term effects of parachute-resisted galloping on heart rate, running speed and stride frequency. Healthy dogs of various breeds were extensively studied in five experimental single cases. The dogs ran on a straight 200 m course with and without resistive drag force applied by a parachute attached to their harness while heart rate, running speed and stride frequency were measured. Subsequently, the measurements were compared to baseline phases at rest. In the present trials we found that heart rate increases similarly with and without parachute-resistance while dogs galloped at lower speeds and with increased stride frequency with applied drag force. Our findings lead us to suggest that parachute-resisted galloping is a clinically applicable exercise in healthy dogs to achieve instant cardiorespiratory response. ABSTRACT: Physical fitness is required for canine athletes and working dogs to optimize performance in various disciplines. There is a lack of research on the effects of resistance exercise on cardiorespiratory variables in dogs. The aim of this study was to investigate the immediate effects of parachute-resisted (PR) gallop on heart rate, running speed and stride frequency compared to unresisted (UR) gallop in dogs. Five N-of-1 trials RCTs with alternating interventions were implemented. Dogs ran on a 200 m course with and without resistive force applied by a parachute attached to their harness while cardiac inter-beat intervals (IBI), running speed and stride frequency were measured. The results were visually displayed and interpreted in graphs and percentage of non-overlapping data estimated effect size. Both interventions showed large effects on heart rate compared to resting values. Mean IBI increased (10–17%) during PR gallop compared to UR gallop although this change was small relative to decreased running speed (19–40%) and increased stride frequency (18–63%). Minimum IBI showed no difference between interventions indicating similar maximum heartbeat per minute. In conclusion, parachute-resistance resulted in dogs galloping at lower speeds at the same cardiorespiratory level of intensity, which may be useful in canine physical rehabilitation and fitness training.